Legal Protection of The Rights of Indonesian Citizens for Children in Lifetime Mixed Marriages - Dian Andriani; Dedy Ardian Prasetyo (International Journal of Social Service and Research, 2023)
This study focuses on the first problem how to determine the principles of ius sanguinis and ius soli in relation to the status of children from mixed marriages, second, how the concept of legal protection for children from mixed marriages in guaranteeing human rights in the future. The method used in this research is normative juridical research with a research approach in the form of a normative approach. The results of the study show that dual citizenship for life is still difficult to do in Indonesia because Article 6 of the citizenship law adheres to the principle of single citizenship. On the principle of "ius sanguinis" has limited dual citizenship arrangements that apply to children resulting from mixed marriages. This application is only valid until the child is 18 years old and is extended by 3 years to avoid being stateless. The state is obliged to fulfill and protect the rights of its citizens, including the right to the citizenship status of children resulting from mixed marriages which is an inseparable part of the conception of human rights contained in the constitution of the 1945 Constitution of the Republic of Indonesia. The concept of legal protection for children resulting from mixed marriages in guaranteeing rights In the future, in making regulations to take special temporary action, the 18 year citizenship law is extended by 3 years and the rights as Indonesian citizens can be protected for life. This is in line with the age that is capable and mature in choosing to become an Indonesian citizen to be able to have their rights in accordance with the legal provisions in force in Indonesia and based on Article 28 H paragraph (2) of the 1945 Constitution of the Republic of Indonesia.